2015
DOI: 10.1021/acs.jafc.5b04093
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Acid Herbicides Using Modified QuEChERS with Fast Switching ESI+/ESI LC-MS/MS

Abstract: A method for the determination of 35 acid herbicides in food matrices was developed, validated, and implemented. It utilizes a modified QuEChERS extraction procedure coupled with quantitation by liquid chromatography tandem mass spectrometry (LC-MS/MS). The acid herbicides analyzed are all organic carboxylic acids, including the older chlorophenoxy acid herbicides such as 2,4-dichlorophenoxyacetic acid (2,4-D), dicamba, 4-chlorophenoxyacetic acid (4-CPA), quinclorac, and many of the newer imidazolinone herbici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Besides that, to develop a reliable multi-residue method that can sufficiently extract acidic pesticides from cereals, the pH of the extraction is also important and should be suitably controlled. There are many published methods [ 33 , 34 , 35 ] for the analysis of acidic herbicides in cereals and related matrices recommended extraction with acidified solvent because acidic herbicides were more stable at low pH. Other authors reported that extract acidic herbicides with alkaline hydrolysis which could break up any covalent bond between the matrix components and acidic pesticides [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides that, to develop a reliable multi-residue method that can sufficiently extract acidic pesticides from cereals, the pH of the extraction is also important and should be suitably controlled. There are many published methods [ 33 , 34 , 35 ] for the analysis of acidic herbicides in cereals and related matrices recommended extraction with acidified solvent because acidic herbicides were more stable at low pH. Other authors reported that extract acidic herbicides with alkaline hydrolysis which could break up any covalent bond between the matrix components and acidic pesticides [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sub-picogram level detection of dicamba from water was also reported using paired-ion electrospray ionization (ESI) mass spectrometry [ 14 ]. Furthermore, several MS-based dicamba analytical methods have been reported for food items [ 17 , 18 ], water and agricultural cleanouts [ 13 , 14 , 16 , 19 , 20 , 21 , 22 ], air samplers [ 6 , 23 , 24 ], crops like apple, pepper, brown rice, and soybean [ 25 ], tobacco [ 26 ], barley [ 27 ], soybean [ 28 ], rice [ 29 ], as well as in other agricultural commodities [ 30 ]. Most of these protocols rely on triple quadrupole and/or higher resolution MS instruments, although quantification procedures using LC–diode array detection (DAD) [ 24 ] and single-quadrupole LC–MS [ 6 , 31 ] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to find monofamily methods for the determination of phytohormones (auxins [ 10 , 11 ], cytokinins [ 12 , 13 ], gibberellins [ 14 , 15 ]) or methods specifically developed for the analysis of acidic herbicides [ 16 , 17 , 18 ] in the literature. Some scientific publications have even jointly analyzed various families of phytohormones [ 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%